Akt-mediated phosphorylation of Bmi1 modulates its oncogenic potential, E3 ligase activity, and DNA damage repair activity in mouse prostate cancer - Nacerddine, Karim; Beaudry, Jean-Bernard; Ginjala, Vasudeva; Westerman, Bart; Mattiroli, Francesca; Song, Ji-Ying; Van Der Poel, Henk; Ponz, Olga Balague; Pritchard, Colin; Cornelissen-Steijger, Paulien; Zevenhoven, John; Tanger, Ellen; et al. (The Journal of clinical investigation, 2012)
Prostate cancer (PCa) is a major lethal malignancy in men, but the molecular events and their interplay underlying prostate carcinogenesis remain poorly understood. Epigenetic events and the upregulation of polycomb group silencing proteins including Bmi1 have been described to occur during PCa progression. Here, we found that conditional overexpression of Bmi1 in mice induced prostatic intraepithelial neoplasia, and elicited invasive adenocarcinoma when combined with PTEN haploinsufficiency. In addition, Bmi1 and the PI3K/Akt pathway were coactivated in a substantial fraction of human high-grade tumors. We found that Akt mediated Bmi1 phosphorylation, enhancing its oncogenic potential in an Ink4a/Arf-independent manner. This process also modulated the DNA damage response and affected genomic stability. Together, our findings demonstrate the etiological role of Bmi1 in PCa, unravel an oncogenic collaboration between Bmi1 and the PI3K/Akt pathway, and provide mechanistic insights into the modulation of Bmi1 function by phosphorylation during prostate carcinogenesis.